Comparative anatomical and histological study of the eye lens development in two species of ovoviviparous teleost fishes, Xiphophorous maculatus and Gambusia affinis - Hani Hamoudi; sima almudris (College of Education for Pure Sciences, 2012)
ABSTRACT This study was conducted to explore the comparative development of the eye lens in two species of ovoviviparous teleost fish. The first fish was Gambusia affinis while the second was Xiphophorus maculatus. The results showed that the lens development starts at early stages of development.In both species. The first signal of lens genesis appears at the2nd stage of development, which is seen as spherical solid lens placode in the 1st one fish while in the 2nd fish as irregularly outlined and the radius is less than that of the 1st fish. At the 3rd stage the begining of primary lens fibers synthesis appears at the center of the lens placode in the 1st fish,while in the 2nd one doesn't appear. On the other hand the genesis of the primary fibers appeared in a parallel pattern in the 2nd fish at the 4th stage. At the 5th stage the initiation of lens capsule was shown at the periphery in the 1st fish and secondary lens fibers primordium appeared in 2nd fish. At the 6th stage the following features are seen: progression of primary and secondary lens fibers, straight sutures between the lens fibers in the 1st fish,and the completion of central lens fibers which appeared parallel with straight sutures,as well as thin of lens capsule in the 2nd fish. At the 7th stage in the 1st fish, the spaces between the lens fibers reduced,the Y shaped suture appeared, while in the 2nd fish, the peripheral lens fibers and their lucident spaces were clear and some of it appeared elongated while the other are circled. On the other hand the primary and secondary lens fibers (straigt and circled), the lens epithelium, the lens sutures in the 2nd fish were completed. The 8th stage considered as the final stage of lens development in both species.The lens componens vary some what between the two adult species. In the adult 1st fish the lens was spherical in shape and its components represented as the capsule, subcapsular epithelium and concentric lens fibers, while in the 2nd adult fish the lens was ovoid in shape, the radius is less that of the 1st fish. The complete differentiation of the primary components were completed at the9th stage of development in the 2nd fish.